Enhancing Students’ Literary and Essay Writing Skills through Project-Based Learning: A Qualitative Case Study - Sri Maryani; Erwin Erwin (Institute of Multidisciplinary Research and Community Service, 2026)
This study aims to examine how Project-Based Learning (PjBL) impacts students' literary and essay writing skills in higher education. This study used a qualitative approach with a case study design involving students of the Indonesian Language and Literature Education Study Program. Data were collected through participant observation, semi-structured interviews, and analysis of student writing. The results indicated that implementing PjBL enhanced students' writing skills, especially in developing ideas, organizing texts, language use, and creative writing style. Students actively engaged in collaborative and reflective writing processes, producing authentic works in the form of poems, short stories, drama scripts, and reflective essays. In addition to technical aspects, PjBL also fostered critical thinking skills, creative literacy, self-confidence, and metacognitive awareness. This model also changed students' perceptions of writing, from a rigid academic activity to a meaningful and contextual expressive practice. Despite constraints such as limited time and varying writing abilities, the implementation of scaffolding strategies and the use of digital learning resources proved effective in supporting the learning process. This study concluded that PjBL is an effective pedagogical approach in improving writing skills while promoting holistic learning in higher education. The findings of this study provide important implications for the development of a more innovative, participatory, and 21st-century competency-oriented Indonesian language and literature learning model. Furthermore, this study confirms that integrating authentic projects into learning can create a more meaningful, adaptive, and relevant learning experience for students' academic and social needs. Therefore, Project-Based Learning (PjBL) is recommended as an alternative learning strategy that can be implemented sustainably in teaching writing in higher education. Keywords: Project-Based Learning, writing skills, literary writing, essay writing, qualitative case study